Predictive factors for vaginal delivery in pregnant women with previous cesarean section: a case-control study - Reis, Gabriela Sabbatine [UNESP]; Lopes, Lucas Casagrande Passoni; Vendramini, Eleksandra Cibele Gusman; Damaso, Ênio Luis; Borges, Vera Therezinha Medeiros [UNESP] (Federação das Associações de Ginecologia e Obstetrícia, 2025)
Objective: To identify factors that predict the likelihood of a successful vaginal birth after cesarean section (VBAC). Methods: An observational, case-control study was conducted at Hospital das Clínicas, Botucatu Medical School, a tertiary referral center in Brazil. Medical records of women with singleton term pregnancies, one previous cesarean section, and a live fetus in cephalic presentation who delivered between January 2013 and December 2015 were reviewed. Participants were classified according to delivery mode: vaginal birth after cesarean section or repeat cesarean section. Maternal demographics, clinical and obstetric characteristics, and neonatal outcomes were analyzed. Associations were assessed using chi-square, and significant variables were entered into a multivariate logistic regression model. Results: A total of 653 women met the inclusion criteria. Of these, 324(49.6%) achieved a vaginal birth, and 329(50.4%) underwent a repeat cesarean section. Factors associated with a higher likelihood of vaginal birth included a history of prior vaginal delivery, cervical dilation of at least 4 cm at admission, a Bishop score of 6 or higher, spontaneous onset of labor, absence of chronic hypertension, and neonates classified as appropriate or small for gestational age. In contrast, advanced maternal age, unemployment, diabetes, and hypertensive disorders were associated with an increased likelihood of cesarean delivery. Conclusion: VBAC was more likely in women with cervical dilation of 4 cm or more at admission, a Bishop score of 6 or higher, a history of vaginal birth, spontaneous labor onset, absence of chronic hypertension, and lower neonatal birth weight.